Effect of Cobalt–Chromium–Molybdenum Implant Surface Modifications on Biofilm Development of S. aureus and S. epidermidis - Paulitsch-Fuchs, Astrid H.; Bödendorfer, Benjamin; Wolrab, Lukas; Eck, Nicole; Dyer, Nigel P.; Lohberger, Birgit (Frontiers in Cellular and Infection Microbiology, 2022)
Periprosthetic infections are an eminent factor in patient care and also having significant economic implications. The number of biofilm-infection related replacement surgeries is increasing and will continue to do so in the following decades. To reduce both the health burden of the patients and the costs to the healthcare sector, new solutions for implant materials resistant to such infections are necessary. This study researches different surface modifications of cobalt–chromium–molybdenum (CoCrMo) based implant materials and their influence on the development of biofilms. Three smooth surfaces (CoCrMo, CoCrMo TiN, and CoCrMo polished) and three rough surfaces (CoCrMo porous coated, CoCrMo cpTi, and CoCrMo TCP) are compared. The most common infectious agents in periprosthetic infections are Staphylococcus aureus and Coagulase-negative staphylococci (e.g., Staphylococcus epidermidis), therefore strains of these two species have been chosen as model organisms. Biofilms were grown on material disks for 48 h and cell number, polysaccharide content, and protein contend of the biofilms were measured. Additionally, regulation of genes involved in early biofilm development (S. aureus icaA, icaC, fnbA, fnbB, clfB, atl; S. epidermidis atlE, aap) was detected using RT-q-PCR. All results were compared to the base alloy without modifications. The results show a correlation between the surface roughness and the protein and polysaccharide content of biofilm structures and also the gene expression of the biofilms grown on the different surface modifications. This is supported by the significantly different protein and polysaccharide contents of the biofilms associated with rough and smooth surface types. Additionally, early phase biofilm genes (particularly icaA, icaC, and aap) are statistically significantly downregulated compared to the control at 48 h on rough surfaces. CoCrMo TiN and polished CoCrMo were the two smooth surface modifications which performed best on the basis of low biofilm content.